Algal biomass-loaded hydrogel scaffolds as a biomimetic platform with antibacterial and wound healing activities - Agarwal, Aakanksha; Kumar, Arun; Garg, Piyush; Chakraborty, Arnab; Verma, Ranjan; Sarwat, Maryam; Gupta, Ajay; Sasmal, Pijus K.; Verma, Yogesh Kumar; Chowdhury, Chiranjit; Mukherjee, Monalisa (ACS Applied Polymer Materials, 2022)
The confluence of hydrogel scaffolds and dried algal biomass (AB), consisting of all the bioactive compounds, offers the possibility to facilitate wound healing while simultaneously instilling antibacterial benefits. For this purpose, a single-step synthesis of algal (Chlorella sorokiniana) biomass-loaded hydrogel scaffolds (AHS) was achieved. C. sorokiniana has been used in different areas for several years and has proved attractive to the pharmaceutical and cosmetic industries. Of note, the presence of phytochemicals and various bioactive compounds provides an added health benefit. Hitherto, we report AHS with accelerated wound healing along with potent anti-inflammatory and antibacterial properties. AHS consisting of different concentrations of AB was applied for 14 days on excisional wounds in mice. Microscopic analyses, assessment of proinflammatory and anti-inflammatory cytokines, and histological studies were performed to investigate wound healing. These scaffolds were extensively characterized and studied using Fourier transform infrared, X-ray diffraction, Raman, atomic force microscopy, transmission electron microscopy, scanning electron microscopy, swelling, rheological, thermal, and mechanical analyses. AHS have excellent biocompatibility in addition to significant antibacterial activity against Escherichia coli (99%) and Staphylococcus aureus (98%). We believe that the as-synthesized AHS have the potential to broaden the arsenal of more effective wound healing processes along with antibacterial activities.
Keywords: antibacterial activity; Biomass; hydrogel scaffold; microalgae; wound Healing

Microbial production of N-acetyl-D-glucosamine (GlcNAc) for versatile applications: biotechnological strategies for green process development - Das, Sancharini; Chowdhury, Chiranjit; Kumar, S. Pavan; Roy, Debasis; Gosavi, Suresh W.; Sen, Ramkrishna (Carbohydrate Research, 2024)
N-acetyl-D-glucosamine (GlcNAc) is a commercially important amino sugar for its wide range of applications in pharmaceutical, food, cosmetics and biofuel industries. In nature, GlcNAc is polymerised into chitin biopolymer, which is one of the major constituents of fungal cell wall and outer shells of crustaceans. Sea food processing industries generate a large volume of chitin as biopolymeric waste. Because of its high abundance, chitinaceous shellfish wastes have been exploited as one of the major precursor substrates of GlcNAc production, both in chemical and enzymatic means. Nevertheless, the current process of GlcNAc extraction from shellfish wastes generates poor turnover and attracts environmental hazards. Moreover, GlcNAc isolated from shellfish could not be prescribed to certain groups of people because of the allergic nature of shell components. Therefore, an alternative route of GlcNAc production is advocated. With the advancement of metabolic construction and synthetic biology, microbial synthesis of GlcNAc is gaining much attention nowadays. Several new and cuttingedge technologies like substrate co-utilization strategy, promoter engineering, and CRISPR interference system were proposed in this fascinating area. The study would put forward the potential application of microbial engineering in the production of important pharmaceuticals. Very recently, autotrophic fermentation of GlcNAc synthesis has been proposed. The metabolic engineering approaches would offer great promise to mitigate the issues of low yield and high production cost, which are major challenges in microbial bio-processes industries. Further process optimization, optimising metabolic flux, and efficient recovery of GlcNAc from culture broth, should be investigated in order to achieve a high product titer. The current study presents a comprehensive review on microbe-based eco-friendly green methods that would pave the way towards the development of future research directions in this field for the designing of a cost-effective fermentation process on an industrial setup.
Keywords: Genetic engineering; GlcNAc applications; Market status; Microbial bioprocess; N-acetyl-D-glucosamine; synthetic biology

Potential utility of bacterial protein nanoreactor for sustainable in-situ biocatalysis in wide range of bioprocess conditions - Shinde, Yashodhara D.; Chowdhury, Chiranjit (Enzyme and microbial technology, 2024)
Bacterial microcompartments (MCPs) are proteinaceous organelles that natively encapsulates the enzymes, substrates, and cofactors within a protein shell. They optimize the reaction rates by enriching the substrate in the vicinity of enzymes to increase the yields of the product and mitigate the outward diffusion of the toxic or volatile intermediates. The shell protein subunits of MCP shell are selectively permeable and have specialized pores for the selective inward diffusion of substrates and products release. Given their attributes, MCPs have been recently explored as potential candidates as subcellular nano-bioreactor for the enhanced production of indus-trially important molecules by exercising pathway encapsulation. In the current study, MCPs have been shown to sustain enzyme activity for extended periods, emphasizing their durability against a range of physical challenges such as temperature, pH and organic solvents. The significance of an intact shell in conferring maximum pro-tection is highlighted by analyzing the differences in enzyme activities inside the intact and broken shell. Moreover, a minimal synthetic shell was designed with recruitment of a heterologous enzyme cargo to demonstrate the improved durability of the enzyme. The encapsulated enzyme was shown to be more stable than its free counterpart under the aforementioned conditions. Bacterial MCP-mediated encapsulation can serve as a potential strategy to shield the enzymes used under extreme conditions by maintaining the internal microen-vironment and enhancing their cycle life, thereby opening new means for stabilizing, and reutilizing the enzymes in several bioprocess industries.
Keywords: Bioprocess industries; Encapsulation; Enzyme recycling; Enzyme Stability; Microcompartment; Nanobioreactor

Systemic review on fitness and survival of salmonella in dynamic environment and conceivable ways of its mitigation - Sutar, Ajit A.; Dashpute, Rohit S.; Shinde, Yashodhara D.; Mukherjee, Srestha; Chowdhury, Chiranjit (Indian Journal of Microbiology, 2024)
Gastroenteritis caused by non-typhoidal Salmonella still prevails resulting in several recent outbreaks affecting many people worldwide. The presence of invasive non-typhoidal Salmonella is exemplified by several characteristic symptoms and their severity relies on prominent risk factors. The persistence of this pathogen can be attributed to its broad host range, complex pathogenicity and virulence and adeptness in survival under challenging conditions inside the host. Moreover, a peculiar aid of the ever-changing climatic conditions grants this organism with remarkable potential to survive within the environment. Abusive use of antibiotics for the treatment of gastroenteritis has led to the emergence of multiple drug resistance, making the infections difficult to treat. This review emphasizes the importance of early detection of Salmonella, along with strategies for accomplishing it, as well as exploring alternative treatment approaches. The exceptional characteristics exhibited by Salmonella, like strategies of infection, persistence, and survival parallelly with multiple drug resistance, make this pathogen a prominent concern to human health.
Keywords: Antibiotic resistance; Gastroenteritis; Non-typhoidal Salmonella; pathogenesis; Plant-derived metabolites; Salmonella pathogenicity islands; Type III secretion system

Green synthesis and characterization of gold nanoparticles using pomegranate peel extract for inhibition of calcium oxalate crystals and uropathogenic bacteria - Mundhewadikar, Dhananjay M.; Bhalerao, Minal R.; Vairale, Shiva; Sabir, Safiya; Mote, Chandrashekhar; Chowdhury, Chiranjit; Agawane, Sachin B. (BioNanoScience, 2025)
This study explores the therapeutic potential of pomegranate peel extract (PPE) and its gold nanoparticle conjugate (PPE-AuNP) in the prevention and treatment of urolithiasis. Pomegranate peels collected from four agro-climatic zones of India exhibited consistent methanolic extract yields (10–17%) and total phenolic content, with the highest levels observed in the West zone. Green synthesis of PPE-AuNPs was confirmed through UV–Vis spectroscopy (λmax = 522 nm), DLS (38.2 ± 2.1 nm), zeta potential (-33.66 ± 2.97 mV), and TEM imaging, which showed uniform spherical nanoparticles. Characterization confirmed that PPE-AuNPs were crystalline and phytochemically capped. FTIR shifts in O–H, C = O, and C–O bands, along with a ~ 500 cm-1 Au–O/N vibration, confirmed phytochemical-mediated reduction and stabilization. XRD revealed an FCC structure with a dominant (111) plane, indicating high crystallinity. The synthesized nanoparticles demonstrated antioxidant activity with an IC50 of 21.53 µg/mL, superior to PPE and AuNP alone. In vitro calcium oxalate crystallization assays revealed significant crystal inhibition by PPE-AuNPs, confirmed via E-SEM, EDAX, and XRD analyses. Antibacterial studies against E. coli, K. pneumoniae, S. aureus, and uropathogenic E. coli showed MIC values of 31.25–62.5 µg/mL for PPE and PPE-AuNPs, with negligible activity from AuNP alone. In vivo studies in ethylene glycol-induced urolithiatic rats revealed significant improvement in urinary parameters, renal biochemistry (creatinine, urea, SGPT, SGOT), hematological markers, and histopathology, especially in the PPE-AuNP-treated group. PPE-AuNP treatment normalized urinary appearance, reduced serum creatinine and blood urea nitrogen (BUN), and restored renal architecture with minimal degeneration. The enhanced therapeutic effects of PPE-AuNPs are attributed to their bioactive phenolic surface ligands and colloidal stability. Overall, this study demonstrates the synergistic efficacy of PPE-AuNPs as a potent, green nanotherapeutic agent for urolithiasis, offering antioxidant, antibacterial, and nephroprotective effects with promising translational relevance.